Nitrosatable Drug Exposure during Pregnancy and Preterm and Small‐for‐Gestational‐Age Births. Issue 1 (10th December 2014) - Vuong, Ann M.; Shinde, Mayura U.; Brender, Jean D.; Shipp, Eva M.; Huber, John C; Zheng, Qi; McDonald, Thomas J.; Sharkey, Joseph R.; Hoyt, Adrienne T.; Werler, Martha M.; Kelley, Katherine E.; Langlois, Peter H.; et al.
Abstract Background Nitrosatable drugs react with nitrite in the stomach to form N‐nitroso compounds, observed in animal models to result in adverse pregnancy outcomes, such as birth defects and reduced fetal weight. Previous studies examining prenatal exposure to medications classified as nitrosatable have reported an increased risk of preterm births (PTBs) and small‐for‐gestational‐age (SGA) infants. Methods Using data from mothers (controls) of babies without major birth defects from the National Birth Defects Prevention Study, prenatal nitrosatable drug usage by trimester and month of gestation was examined in relation to PTBs and SGA infants. Results Positive associations were observed with nitrosatable drug use and PTBs, with the strongest relationship with second trimester exposure (adjusted hazard ratio [aHR] 1.37, [95% confidence interval (CI) 1.10, 1.70]). Of the nitrosatable functional groups, secondary amines were the most notable, with a higher association among women with second (aHR 1.37, [95% CI 1.05, 1.79]) and third (aHR 1.34, [95% CI 1.02, 1.76]) trimester exposure compared with women with no prenatal nitrosatable drug use. Among SGA infants, a borderline association was noted with amide exposure during the third trimester (adjusted odds ratio 1.43 [95% confidence interval [CI] 1.00, 2.05]). Conclusions Prenatal exposure to nitrosatable drugs during the second and third trimester of pregnancy, particularly secondary amines, might increase the risk of PTBs. However, prenatal exposure to nitrosatable drugs was not associated with SGA infants, with the exception of amide drugs.